Prevalence, Severity, and Correlates of Suicidal Ideation Among Men and Women in Batterer Intervention Programs - Wolford-Clevenger, Caitlin (Partner Abuse, 2017)
Despite the robust association found between intimate partner violence perpetration and suicidal ideation (Ilgen et al., 2009), the understanding of the development of suicidal ideation among men and women court-mandated to attend batterer intervention programs is limited. Guided by the alcohol myopia model (Josephs & Steele, 1990) and escape theory of suicide (Baumeister, 1990), this cross-sectional study examined the prevalence and severity of suicidal ideation and whether alcohol problems strengthen the relationship between depressive symptoms and suicidal ideation. Surveys were administered to 470 men and women court-mandated to attend batterer intervention programs. Results indicated that 33% of the sample experienced suicidal ideation (15% active ideation) during the 2 weeks prior to batterer intervention program entry. Moderation analyses indicated that as alcohol problems increased, the relationship between depressive symptoms and suicidal ideation strengthened. This work aids practitioners in assessing suicidal ideation in batterer intervention settings.